Economic governance in an enlarged euro area - Begg, Iain.; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2008)
Ten years on from its launch, it is clear that EMU, which has to be regarded as a more profound regime change than is often acknowledged, has had a pronounced effect on economic governance. As a framework for the conduct of macroeconomic policy, EMU has had undoubted successes in assuring price stability and in instilling greater fiscal discipline, yet it is open to the criticism that it has not (yet?) delivered improved performance in the real economy. Moreover, some of the compromises made at the outset and over the twenty years since the roadmap for EMU was first set out, notably to reconcile divergent French and German preferences, have left certain elements of the policy architecture unresolved. In the coming years, several more Member States are expected to become full participants in EMU, so that fresh thinking on the governance arrangements is warranted, not least to accommodate the rather different economic characteristics of the candidate countries.
Economic Papers